Experience-oriented food design in a restaurant context: A study of guest reflections on a fine dining starter - Merkl, Marta; Horvath, Dora; Cosovan, Attila (Journal of Food Technology Research, 2026)
Experience plays a crucial role in our food choices and therefore deserves special attention in related tourism innovation. One possible approach to innovation is food design, a complex design activity aimed at creating different products and services related to food and dining. The area of food design in a restaurant has not been explored in depth. This study provides new insights into the experience design of a fine dining restaurant undergoing metamorphosis, particularly in one case, its opening dinners in Winter 2021/2022. The aim of the paper is to broaden our knowledge of dining experiences, for which ethnography and interactive menu cards as specific questionnaires (2261 responses from 20 dinners, with 303 entries specifically pertaining to the dish investigated) are effective methods. The paper introduces the restaurant context, furthermore the food design classification by Francesca Zampollo. The analysis considers the theory of experience economy by B. Joseph Pine II and James H. Gilmore and their followers, and the results reported here emphasize the importance of “customized” interactivity. The findings of this investigation underline the concept of flow by Mihály Csíkszentmihályi in terms of sensory perceptions. These results are not only relevant to the hospitality industry and the restaurant in question, but can also be utilized more widely in the design of other diets.